"Wybór Heraklesa" jako opowieść fundująca model pracy nad dylematem w doradztwie filozoficznym i coachingu = "The Herakles`es Choise" as a story founding a model of work on a dilemma in philosophical counseling and coaching - Walczak, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article introduces the Y-Model, a novel method employed within the context of philosophical counseling or coaching sessions to address dilemmas faced by individuals. Drawing inspiration from the ancient tale of Heracles at the crossroads, wherein a young hero confronts the pivotal task of selecting his life`s path, this model deconstructs the narrative to identify key decision-making phases.
Keywords: doradztwo filozoficzne; coaching; praca nad dylematem; proces decyzyjny; narzędzia coachingowe; philosophical counseling; working on a dilemma; decision-making process; coaching tools